f ( x ) = n = 1 ∏ ∞ cos ( 2 n + 1 x ) = n = 1 ∏ ∞ 3 1 ( 1 + 2 cos ( 3 n x ) ) = n = 1 ∏ ∞ 2 1 ( cos ( 2 1 4 n x ) + cos ( 2 3 4 n x ) ) = n = 1 ∏ ∞ 5 1 ( 1 + 2 cos ( 5 n x ) + 2 cos ( 5 n 2 x ) ) = n = 1 ∏ ∞ 3 1 ( cos ( 2 1 6 n x ) + cos ( 2 3 6 n x ) + cos ( 2 5 6 n x ) ) = ⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ n = 1 ∏ ∞ ⎝ ⎛ r 1 k = − 2 r − 1 ∑ 2 r − 1 cos ( r n k x ) ⎠ ⎞ n = 1 ∏ ∞ ⎝ ⎛ r 1 k = − 2 r + 1 ∑ 2 r cos ( ( k − 2 1 ) r n x ) ⎠ ⎞ for odd integers r > 1 for even integers r > 1 .
Prove that the above family of products equate one another and find
∫ 0 2 π x f ( x ) d x .
Inspiration: MIT Integration Bee 2015
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(I'll solve the integral first, will figure out the identities later.)
Note that
sin 2 i + 1 x n = 1 ∏ i cos 2 n + 1 x = sin 2 i + 1 x cos 2 i + 1 x n = 1 ∏ i cos 2 n x = 2 1 sin 2 i x cos 2 i x n = 1 ∏ i − 1 cos 2 n x = 2 2 1 sin 2 i − 1 x cos 2 i − 1 x n = 1 ∏ i − 2 cos 2 n x = ⋯ = 2 k 1 sin 2 i + 1 − k x cos 2 i + 1 − k x n = 1 ∏ i − k cos 2 n x = ⋯ = 2 i 1 sin 2 x .
Thus,
f ( x ) = i → ∞ lim n = 1 ∏ i cos 2 n + 1 x = i → ∞ lim 2 i sin 2 i + 1 x sin 2 x = sin 2 x 2 i → ∞ lim 2 i sin 2 i + 1 x 1 = sin 2 x j → ∞ lim j sin 2 j x 1 (let j = 2 i ) = sin 2 x j → ∞ lim sin 2 j x j 1 = sin 2 x j → ∞ lim − 2 j 2 x cos 2 j x − j 2 1 (applying L’Hopital’s rule) = sin 2 x j → ∞ lim x cos 2 j x 2 = x 2 sin 2 x ,
and
∫ 0 2 π x f ( x ) d x = ∫ 0 2 π x ( x 2 sin 2 x ) d x = ∫ 0 2 π 2 sin 2 x d x = [ − 4 cos 2 x ] 0 2 π = − 4 cos π + 4 cos 0 = 8 .
This isn't the complete solution though, you haven't proven the other products
Problem Loading...
Note Loading...
Set Loading...
Lemma (left as an exercise for the reader)
n = 1 ∏ N k = 0 ∑ r − 1 x r n k = k = 0 ∑ r N − 1 x r N k
For odd r :
n = 1 ∏ ∞ ⎝ ⎜ ⎛ r 1 k = − 2 r − 1 ∑ 2 r − 1 cos ( r n k x ) ⎠ ⎟ ⎞ = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r − 1 ∑ 2 r − 1 cos ( r n k x ) = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r − 1 ∑ 2 r − 1 2 e i r n k x + e − i r n k x = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r − 1 ∑ 2 r − 1 e i r n k x = N → ∞ lim n = 1 ∏ N r 1 exp ( − i 2 r − 1 ⋅ r n x ) k = 0 ∑ r − 1 e i r n k x = J
For even r :
n = 1 ∏ ∞ ⎝ ⎜ ⎛ r 1 k = − 2 r + 1 ∑ 2 r cos ( ( k − 2 1 ) r n x ) ⎠ ⎟ ⎞ = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r + 1 ∑ 2 r cos ( ( k − 2 1 ) r n x ) = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r + 1 ∑ 2 r 2 e i ( k − 2 1 ) r n x + e − ( k − 2 1 ) r n x = N → ∞ lim n = 1 ∏ N r 1 k = − 2 r + 1 ∑ 2 r e i ( k − 2 1 ) r n x = N → ∞ lim n = 1 ∏ N r 1 exp ( − i 2 r − 1 ⋅ r n x ) k = 0 ∑ r − 1 e i k r n x = J
So:
J = N → ∞ lim n = 1 ∏ N r 1 exp ( − i 2 r − 1 ⋅ r n x ) k = 0 ∑ r − 1 e i k r n x = N → ∞ lim exp ( − i x 2 1 − r − N ) ⋅ r N 1 n = 1 ∏ N k = 0 ∑ r − 1 e i r n k x = N → ∞ lim exp ( − i x 2 1 − r − N ) ⋅ r N 1 k = 0 ∑ r N − 1 e i r N k x = exp ( 2 − i x ) ⋅ ∫ 0 1 e i x y d y = e − 2 i x ⋅ i x 1 ( e i x − 1 ) = i x 1 ( e 2 i x − e − 2 i x ) = x 2 sin ( 2 x ) Via Lemma Via Riemann Sum
Finally:
∫ 0 2 π x f ( x ) = ∫ 0 2 π 2 sin ( 2 x ) = 8